2019
DOI: 10.1634/theoncologist.2018-0567
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profile of ResectedEGFR-Mutated Lung Adenocarcinoma by Next-Generation Sequencing

Abstract: Background The efficacy of adjuvant targeted therapy for operable lung cancer is still under debate. Comprehensive genetic profiling is needed for detecting co‐mutations in resected epidermal growth factor receptor (EGFR)‐mutated lung adenocarcinoma (ADC), which may interfere the efficacy of adjuvant tyrosine kinase inhibitor (TKI) treatment. Materials and Methods Mutation profiling of 416 cancer‐relevant genes was conducted for 139 resected stage I–IIIa lung ADCs with EGFR mutations using targeted next‐genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…20 Recent data have indicated that approximately one third of EGFR mutationpositive tumors will carry genetic alterations involving EGFR downstream effectors or bypass pathways such as PIK3CA, BRCA1, and NOTCH that could lead to the development of TKI-resistant subclones. 21 Accordingly, a rationale exists for the development of treatment strategies that will target multiple intracellular signaling pathways in EGFR mutation-positive NSCLC.…”
Section: First-generation Egfr Tkismentioning
confidence: 99%
“…20 Recent data have indicated that approximately one third of EGFR mutationpositive tumors will carry genetic alterations involving EGFR downstream effectors or bypass pathways such as PIK3CA, BRCA1, and NOTCH that could lead to the development of TKI-resistant subclones. 21 Accordingly, a rationale exists for the development of treatment strategies that will target multiple intracellular signaling pathways in EGFR mutation-positive NSCLC.…”
Section: First-generation Egfr Tkismentioning
confidence: 99%
“…[24][25][26] TP53, the encoding gene of p53 protein, is the most commonly mutated gene in multiple cancers and is subsistent in approximately 37%-50% LUAD cases. [27][28][29] Mutant p53 potentially triggers chromosomal/genomic instability and further results in a high TMB, which is frequently related to more aggressive malignancy and unsatisfactory prognosis in LUAD. [30][31][32] Nevertheless, several studies have highlighted that TP53-mutated LUAD is characterized with higher PD-L1 expression by malignant cells, boosted T-cell infiltration and tumor immunogenicity, leading to an increased response to ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…The products of p53 target genes are proved to participate in a sequence of crucial biological pathways, including cell proliferation and apoptosis, DNA damage repair, anti‐oxidant function, metabolism and angiogenesis as well as immunoreaction, thus making contributions to the tumor‐suppression effect of p53 24‐26 . TP53, the encoding gene of p53 protein, is the most commonly mutated gene in multiple cancers and is subsistent in approximately 37%‐50% LUAD cases 27‐29 . Mutant p53 potentially triggers chromosomal/genomic instability and further results in a high TMB, which is frequently related to more aggressive malignancy and unsatisfactory prognosis in LUAD 30‐32 .…”
Section: Introductionmentioning
confidence: 99%
“…SnaPShot and next‐generation sequencing, the sensitivity of SnaPshot for KRAS mutation detection was about 10%, but this method is also laborious and time‐consuming 16,17 . Next‐generation sequencing is relatively expensive, time‐consuming, and complicated data interpreting 18,19 . Choong et al detected the KRAS mutations using the isothermal‐based optical sensor for companion diagnostics, 20 a rapid, specific, and sensitive method, but the preparation process is relatively complex and the result is not easy to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Next-generation sequencing is relatively expensive, time-consuming, and complicated data interpreting. 18,19 Choong et al detected the KRAS mutations using the isothermal-based optical sensor for companion diagnostics, 20 a rapid, specific, and sensitive method, but the preparation process is relatively complex and the result is not easy to interpret. Therefore, a high-throughput, economical, sensitive, and easy data analysis assay is urgently needed.…”
mentioning
confidence: 99%